Imbalance of sediment transport in a meso-tidal bay: effect of tidal pumping and residual circulation - Kim, Su In; Seo, Jun Young; Park, Jae-Hun; Kim, Pyeong Joong; Kim, In Gwon; Kim, Kyung Man; Ha, Ho Kyung (Frontiers in Marine Science, 2024)
In-situ mooring systems with acoustic Doppler current profilers were installed in the western (TM01) and eastern (TM02) parts of Yeosu Bay from September 3 to October 2, 2021, to understand the controlling mechanisms of suspended sediment transport. In the bay, freshwater from the Seomjin River freely exchanges with seawater from the open sea. Over the mooring period, current flows were mainly dominated by ebb tides. Power spectral density analysis of the suspended sediment concentration (SSC) exhibited a quarter-diurnal (6.21 h) frequency at TM01 and a semi-diurnal (12.42 h) frequency at TM02. The results suggested that SSC variations in the western part were driven primarily by local sediment resuspension, while they were influenced predominantly by horizontal advection in the eastern part. Differences in SSC variation at the two stations could be due to the physical properties of the bed sediments (TM01: sandy mud containing shell fragments, TM02: mud). Such current flows and SSC variations over the tidal cycles caused an imbalance of sediment transport. At TM01, the sediment fluxes were dominant seaward tidal pumping (88% of the total) and the discharge of suspended sediments in the surface layer by residual circulation. At TM02, landward sediment fluxes were driven primarily by the residual current (73% of the total). Although the suspended sediment fluxes tended to be compensated and balanced mutually by circulation over the entire period, the suspended sediment fluxes at TM02 were approximately twice higher than those at TM01. This was caused by the difference in SSC asymmetry of flood and ebb at the two stations. The mechanisms controlling the transport of suspended sediment could vary spatially, and the relative contribution of tidal pumping and residual circulation could result in an imbalance of sediment transport.